A profile about the recent expansion of higher education in Brazil: democratic and inclusive aspects - Marques, Antonio Carlos Henriques; Cepêda, Vera Alves (Universidade Estadual Paulista / UNESP, 2013)
This paper seeks to analyze the scenario and objectives that guide the recent expansion of public higher education in Brazil, especially in the growth segment of the federal universities (IFES). The cutout in this segment is legitimized by the bond of the IFES with the federal government policy, endowed with resources – economic, legal and regulatory – capable of to produce profound changes in direct and indirect forms in the higher education system in the national plan. The broad and forceful action by the federal government in the last decade may represent a state policy, conscious and concerted to the area of higher education. Under this hypothesis, we tried to detect the quantitative impact of expansion and its qualitative strategies – especially the theme of inclusion and reduction of social inequalities and cultural inequalities starting from new bases of access, entry, stay and telos of the performance of public universities.